2005
DOI: 10.1016/j.clim.2005.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Armed CD4+ Th1 effector cells and activated macrophages participate in bile duct injury in murine biliary atresia

Abstract: Biliary atresia (BA) is an inflammatory cholangiopathy of infancy. A proposed mechanism regarding the pathogenesis of BA is that of a virus-induced, immune-mediated injury to bile ducts. The rotavirus (RRV)-induced murine model of BA was utilized to determine the hepatic inflammatory response related to ductal obstruction and if the immune response recapitulated human BA. One week after infection, there was a significant increase in liver CD4 + T cells producing IFN-γ and in macrophages producing TNF-α. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
89
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(99 citation statements)
references
References 27 publications
(37 reference statements)
10
89
0
Order By: Relevance
“…19 There has been some clinical and experimental evidence that BA exhibits a polarized, specifically Th1 immune response, at least in the early stages of the disease (i.e., up to the time of KP). 16,20,21,22 For instance, Mack et al 16 using immunocytochemistry and RT-PCR showed a CD4ϩ and CD8ϩ T cell infiltrate within portal tracts with a localized increased expression of the cytokines IL-2, IFN␥, TNF␣ and IL-12 (but not IL-4 or IL-5). Experimentally (using a rotavirus-induced murine BA model) the same group 20 has shown significant increases in CD4ϩ T cells producing IFN␥ (i.e., Th1 response) with a later influx of activated macrophages producing TNF␣.…”
Section: Discussionmentioning
confidence: 99%
“…19 There has been some clinical and experimental evidence that BA exhibits a polarized, specifically Th1 immune response, at least in the early stages of the disease (i.e., up to the time of KP). 16,20,21,22 For instance, Mack et al 16 using immunocytochemistry and RT-PCR showed a CD4ϩ and CD8ϩ T cell infiltrate within portal tracts with a localized increased expression of the cytokines IL-2, IFN␥, TNF␣ and IL-12 (but not IL-4 or IL-5). Experimentally (using a rotavirus-induced murine BA model) the same group 20 has shown significant increases in CD4ϩ T cells producing IFN␥ (i.e., Th1 response) with a later influx of activated macrophages producing TNF␣.…”
Section: Discussionmentioning
confidence: 99%
“…10, 11 As seen in children with biliary atresia, livers of neonatal mice with experimental atresia undergo expansion of CD3+ cells and overexpress Ifng at the time of duct obstruction. 8, 19 We previously reported that the loss of Ifng attenuates the tropism of lymphocytes to bile ducts and prevents the development of the biliary atresia phenotype. 10 Therefore, we hypothesized that neonatal hepatic CD3+ cells that express Ifng induce the development of biliary atresia.…”
Section: Neonatal Induction Of Ifng By Hepatic Cd4+ and Cd8+ Cells Inmentioning
confidence: 99%
“…6 A similar T helper 1 response is replicated in the most promising animal model of BA, the rhesus rotavirus-infected newborn mouse model. [7][8][9] The innate immune response is also activated in the human BA liver, as demonstrated by the later appearance of cells of the CD68ϩ macrophage/ monocyte family in portal tracts and evidence of chemokine and cytokine release by these and related cells. 7 Abnormal expression of cellular adhesion molecules (intercellular cell adhesion molecule, CD54, vascular cell adhesion molecule, CD62E) on biliary epithelium and vascular endothelium and elevated circulating levels of soluble adhesion molecules have also been observed.…”
mentioning
confidence: 99%
“…[7][8][9] The innate immune response is also activated in the human BA liver, as demonstrated by the later appearance of cells of the CD68ϩ macrophage/ monocyte family in portal tracts and evidence of chemokine and cytokine release by these and related cells. 7 Abnormal expression of cellular adhesion molecules (intercellular cell adhesion molecule, CD54, vascular cell adhesion molecule, CD62E) on biliary epithelium and vascular endothelium and elevated circulating levels of soluble adhesion molecules have also been observed. 10 Furthermore, a variety of other cytokines, chemokines, and growth factors are released that stimulate downstream amplification of the inflammatory cascade and induction of fibrogenesis (Fig.…”
mentioning
confidence: 99%